Antimony Assessment in PET Bottles for Soft Drink - Kiyataka, Paulo Henrique M. (2017)
The aim of this work was to develop a method for the determination of antimony (Sb) in polyethylene terephthalate (PET) bottles and to evaluate its migration into soft drink and simulant. In this context, a new procedure for PET sample preparation, using a high pressure asher (HPA), is presented for the determination of Sb by inductively coupled plasma optical emission spectrometry (ICP-OES). The concentration of Sb in PET bottles ranged between 272 and 650 mg kg−1. The migration of Sb into soft drink after 180 days at 35 °C was below the LOQ, 20 μg L−1. The specific migration of Sb from the bottle into simulant 3% of acetic acid after the contact per 10 days at 40 °C was less than the LOQ, 23.5 μg L−1. The results showed that all packaging evaluated contained Sb, but the maximum permissible migration value for Sb, 40 μg L−1, established by Anvisa and EU, was never exceeded.